Analysis of invasive cervical cancer cases in Latvia - Kornete, Anna; Pumpure, Elizabete; Macuks, Ronalds (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of the study is to evaluate the cervical cancer screening programme in Latvia and to determine how early cervical cancer diagnostics can be improved and the burden of the disease can be reduced. Methods: All cervical cancer cases diagnosed in 2014 and treated in Oncology Centre of Latvia were included in the retrospective cross-sectional study. Cervical cancer cases were classified according to the cytological sampling interval: a “short” (<3 years), a “regular” (3–5 years) or a “long” (>5 years) interval. Results: There were 189 patients identified during the study period. Information was obtained from 130 (68.7%) patients. 49.2% (n=64) of all patients had had a cytological examination within the last three years. For 11.6% (n=15) women, the screening interval was regular, while 21.5% (n=28) had had their last cytological examination more than five years before. 17.7% (n=23) had never had cytological examination. A tendency for more frequent early stage cervical cancer detection in the group of cytological sampling interval less than three years compared to a 3–5 years interval (71.9% vs. 53.3%, p=0.003) was observed. Conclusions: In Latvia, cervical cancer is an unresolved healthcare issue for women. Despite the fact that lack of a quality management system, diagnostic imperfections and non-attendance in the organized, cytology-based screening programme remain the main barrier of cervical cancer control, introduction of a more sensitive test, such as primary testing for oncogenic human papilloma virus types, could significantly reduce the burden of the disease.